2013
DOI: 10.5194/acp-13-5117-2013
|View full text |Cite
|
Sign up to set email alerts
|

Dissolved organic carbon (DOC) and select aldehydes in cloud and fog water: the role of the aqueous phase in impacting trace gas budgets

Abstract: Cloud and fog droplets efficiently scavenge and process water-soluble compounds and, thus, modify the chemical composition of the gas and particle phases. The concentrations of dissolved organic carbon (DOC) in the aqueous phase reach concentrations on the order of ~ 10 mgC L−1 which is typically on the same order of magnitude as the sum of inorganic anions. Aldehydes and carboxylic acids typically comprise a large fraction of DOC because of their high solubility. The dissolution of species in the a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 96 publications
3
63
2
Order By: Relevance
“…The median concentration of the DOC content of 14.8 mgC·L −1 (average value: 37.2 mgC· L −1 ) was representative of other radiation fog waters Ervens et al 2013;Straub et al 2012). The fog event collected on 12/01/2012 exhibited a high amount of DOC content with 262.2 mgC·L −1 ; however, this value was consistent with previous values of DOC observed from the same sampling site (Raja et al 2005).…”
Section: Quantification Of Natural Aqueous Samplessupporting
confidence: 86%
See 2 more Smart Citations
“…The median concentration of the DOC content of 14.8 mgC·L −1 (average value: 37.2 mgC· L −1 ) was representative of other radiation fog waters Ervens et al 2013;Straub et al 2012). The fog event collected on 12/01/2012 exhibited a high amount of DOC content with 262.2 mgC·L −1 ; however, this value was consistent with previous values of DOC observed from the same sampling site (Raja et al 2005).…”
Section: Quantification Of Natural Aqueous Samplessupporting
confidence: 86%
“…Although the majority of the samples in this study comprised less than 2 % of the total DOC, as typically found in other fog and cloud water analyses (Deguillaume et al 2014;Ervens et al 2013), the DOC values of these particular events were some of the highest measured in this study, with the maximum DOC (262 mg/L) observed on 12/01/2012. By summing up the identified carbon contributions in the study (all aldehydes and ketones), we determined that on 11/28/12, 12/01/2012, and 12/08/2012 acetone comprised 2.5, 14.4, and 22.4 %, respectively, of the total DOC.…”
Section: Acetone Contribution In Fog Watermentioning
confidence: 71%
See 1 more Smart Citation
“…In these media, organic compounds are known to undergo oxidation by a number of radicals, among which OH radicals are the most reactive oxidants (Herrmann et al, 2010). This reactivity initiates chain reactions that are related to atmospherically important issues such as the oxidizing capacity of the atmosphere (Monod and Carlier, 1999;Monod et al, 2007;Poulain et al, 2010;Ervens et al, 2013), the fate of organic compounds (Blando and Turpin, 2000;Monod et al, 2005) and the formation of secondary organic aerosol (SOA) (Altieri et al, 2006;Carlton et al, 2007;Volkamer et al, 2009;Ervens and Volkamer, 2010;Tan et al, 2010Tan et al, , 2012Lim et al, 2010;Ervens et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Important atmospheric and climatic processes are mediated by organic compounds. Being highly reactive, atmospheric OC affects oxidative and trace element chemistry by changing the lifetimes of radical species (Arakaki et al, ; Ervens et al, ), and by complexing metals (Witt & Jickells, ). The light‐absorbing fractions of OC influence the amount of light reaching the land surface, which is directly related to climate (Kieber, Whitehead, Reid, Willey, & Seaton, ).…”
Section: Introductionmentioning
confidence: 99%